Interactional convergence in conversational storytelling: when reported speech is a cue of alignment and/or affiliation - Guardiola, Mathilde; Bertrand, Roxane (Frontiers in Psychology, 2013)
This paper investigates how and when interactional convergence is established by participants in conversation. We analyze sequences of storytelling using an original method that combines Conversation Analysis and a corpus-based approach. In storytelling, the participant in the position of “listener” is expected to produce either generic or specific responses adapted to the storyteller's narrative. The listener's behavior produced within the current activity is a cue of his/her interactional alignment. We show here that the listener can produce a specific type of (aligned) response, which we term a reported speech utterance in echo. The participant who is not telling the story is nonetheless able to animate the characters, while reversing the usual asymmetric roles of storyteller and listener. The use of this device is a way for the listener to display his/her stance toward the events told by the storyteller. If the listener's stance is congruent with that of the storyteller, this reveals a high degree of affiliation between the participants. We present seventeen excerpts from a collection of 94 instances of Echo Reported Speech (ERS) which we examined using the concepts of alignment and affiliation in order to show how different kinds of convergent sequences are constructed. We demonstrate that this phenomenon is mainly used by the listener to align and affiliate with the storyteller by means of reformulative, enumerative, or overbidding ERS. We also show that in affiliative sequences, reported speech can be used by the listener in a humorous way in order to temporarily disalign. This disalignment constitutes a potential starting point for an oblique sequence, which, if accepted and continued by the storyteller, gives rise to a highly convergent sequence.